The single-cell landscape of immunological responses of CD4+ T cells in HIV versus severe acute respiratory syndrome coronavirus 2. Issue 1 (January 2021) - Collora, Jack A.; Liu, Runxia; Albrecht, Kristen; Ho, Ya-Chi
Abstract : Purpose of review: CD4 + T cell loss is the hallmark of uncontrolled HIV-1 infection. Strikingly, CD4 + T cell depletion is a strong indicator for disease severity in the recently emerged coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We reviewed recent single-cell immune profiling studies in HIV-1 infection and COVID-19 to provide critical insight in virus-induced immunopathogenesis. Recent findings: Cytokine dysregulation in HIV-1 leads to chronic inflammation, while severe SARS-CoV-2 infection induces cytokine release syndrome and increased mortality. HIV-1-specific CD4 + T cells are dysfunctional, while SARS-CoV-2-specific CD4 + T cells exhibit robust Th1 function and correlate with protective antibody responses. In HIV-1 infection, follicular helper T cells (TFH ) are susceptible to HIV-1 infection and persist in immune-sanctuary sites in lymphoid tissues as an HIV-1 reservoir. In severe SARS-CoV-2 infection, TFH are absent in lymphoid tissues and are associated with diminished protective immunity. Advancement in HIV-1 DNA, RNA, and protein-based single-cell capture methods can overcome the rarity and heterogeneity of HIV-1-infected cells and identify mechanisms of HIV-1 persistence and clonal expansion dynamics. Summary: Single-cell immune profiling identifies a high-resolution picture of immune dysregulation in HIV-1 and SARS-CoV-2 infection and informs outcome prediction and therapeutic interventions.